Core Recommendations for Antifungal Stewardship: A Statement of the Mycoses Study Group Education and Research Consortium. (5th August 2020) - Johnson, Melissa D; Lewis, Russell E; Dodds Ashley, Elizabeth S; Ostrosky-Zeichner, Luis; Zaoutis, Theoklis; Thompson, George R; Andes, David R; Walsh, Thomas J; Pappas, Peter G; Cornely, Oliver A; Perfect, John R; Kontoyiannis, Dimitrios P
Abstract: In recent years, the global public health community has increasingly recognized the importance of antimicrobial stewardship (AMS) in the fight to improve outcomes, decrease costs, and curb increases in antimicrobial resistance around the world. However, the subject of antifungal stewardship (AFS) has received less attention. While the principles of AMS guidelines likely apply to stewarding of antifungal agents, there are additional considerations unique to AFS and the complex field of fungal infections that require specific recommendations. In this article, we review the literature on AMS best practices and discuss AFS through the lens of the global core elements of AMS. We offer recommendations for best practices in AFS based on a synthesis of this evidence by an interdisciplinary expert panel of members of the Mycoses Study Group Education and Research Consortium. We also discuss research directions in this rapidly evolving field. AFS is an emerging and important component of AMS, yet requires special considerations in certain areas such as expertise, education, interventions to optimize utilization, therapeutic drug monitoring, and data analysis and reporting.